Improving subseasonal Indian summer monsoon rainfall forecasts with U-Net calibration - Emile D. Esmaili; Andrew W. Robertson; Muhammad Azhar Ehsan; Bohar Singh; Aaron Kaplan; Avijit Dey; Susmitha Joseph (Climate Dynamics, 2026)

Historical characteristics and climate mode modulation of extreme wave climate over Indonesian Maritime continent based on ERA5 reanalysis data - Ahmad Bayhaqi; Mochamad Riza Iskandar; Fuad Azminuddin; Saat Mubarrok; Muhammad Iqbal; Dewi Surinati; Faizal Ade Rahmahuddin Abdullah (Climate Dynamics, 2026)

Convection-permitting climate simulations using SINGV-RCM and WRF over the Maritime Continent - Venkatraman Prasanna; Srivatsan V. Raghavan; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Nguyen Ngoc Son; Bhenjamin Jordan Lozada Ona; Pavan Harika Raavi; Anupam Kumar; Jianjun Yu; Chen Chen; et al. (Climate Dynamics, 2026)

Correction: Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2026)

Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2025)
The climate of the Maritime Continent, including Singapore, is influenced by a wide range of tropical drivers including the El-Niño Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), the Madden–Julian Oscillation (MJO), and equatorial wave activity. In Singapore, the rainfall pattern is often marked by episodes of short intense rainfall bursts, primarily driven by mesoscale convective systems, such as Sumatra squall lines. These episodes often result in local flash floods and strong wind bursts. Here we analyse 33 years of Sumatra squalls affecting Singapore and investigate the potential impact of the main modes of climate variability and atmospheric equatorial tropical waves. Highlighted results are that, on average, Sumatra squalls originate from Sumatra and the Strait of Malacca, make landfall over Singapore primarily in the morning and last about 2 h, and are more frequent from April to November. These squalls tend to be more frequent under La Niña conditions, which are associated with locally warm sea surface temperature anomalies and favourable atmospheric anomalies over the Maritime Continent region. On intraseasonal scale, the MJO may play a role in setting the westerlies and enhancing convective conditions favorable for the squalls to intensify and propagate eastward. Convectively-coupled Kelvin waves are important for the initiation and eastward propagation of the squalls over Sumatra and the Strait of Malacca, while equatorial Rossby, and mixed Rossby gravity waves influence their meridional propagation toward Singapore.

Predictability of the early summer surface air temperature over Western South Asia - Irfan Ur Rashid; Muhammad Adnan Abid; Marisol Osman; Fred Kucharski; Moetasim Ashfaq; Antje Weisheimer; Mansour Almazroui; José Abraham Torres-Alavez; Muhammad Afzaal (Climate Dynamics, 2024)
Variability of the Surface Air Temperature (SAT) over the Western South Asia (WSA) region leads to frequent heatwaves during the early summer (May-June) season. The present study uses the European Centre for Medium-Range Weather Forecast’s fifth-generation seasonal prediction system, SEAS5, from 1981 to 2022 based on April initial conditions (1-month lead) to assess the SAT predictability during early summer season. The goal is to evaluate the SEAS5’s ability to predict the El Niño-Southern Oscillation (ENSO) related interannual variability and predictability of the SAT over WSA, which is mediated through upper-level (200-hPa) geopotential height anomalies. This teleconnection leads to anomalously warm surface conditions over the region during the negative ENSO phase, as observed in the reanalysis and SEAS5. We evaluate SEAS5 prediction skill against two observations and three reanalyses datasets. The SEAS5 SAT prediction skill is higher with high spatial resolution observations and reanalysis datasets compared to the ones with low-resolution. Overall, SEAS5 shows reasonable skill in predicting SAT and its variability over the WSA region. Moreover, the predictability of SAT during La Niña is comparable to El Niño years over the WSA region.

Decadal climate variability of chlorophyll-a in response to different oceanic factors in the Western Indian ocean: the sea of oman - Veeranjaneyula Chinta; Muhsan Ali Kalhoro; Zhenlin Liang; Muhammad Tahir; Guiting Song; Wei Zhang (Climate Dynamics, 2024)

SINGV-RCM: the convection-permitting regional climate model for Singapore - Venkatraman Prasanna; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Xin Rong Chua; Claudio Sanchez; Chen Chen; Jianjun Yu; Harika Pavan Raavi; Fei Luo; Muhammad Eeqmal Hassim; et al. (Climate Dynamics, 2024)
The development of the Singapore regional climate model (SINGV-RCM) is documented in this study. The model’s skill in predicting mean and extreme rainfall over the Maritime Continent at 8 km and 2 km grid resolution is assessed using observed rainfall. The model’s sensitivity to vertical grid and convection parametrization is also evaluated. Results demonstrate the added value of downscaling to 8 and 2 km. The spatial and temporal characteristic of the diurnal rainfall is shown to be in good agreement with the observation. The model also demonstrates skill in capturing extreme rainfall. In general, the rainfall in the 8 km and 2 km simulations are quite similar, when regrided to a coarser resolution. Even then, the convection-permitting simulation at 2 km is found to add value over the 8 km simulation, particularly in capturing the higher rainfall thresholds. Mean biases over the ocean is found to be larger than that over the land, which suggests the need to further tune SINGV-RCM for long climate simulations.

SPEEDY-NEMO: performance and applications of a fully-coupled intermediate-complexity climate model - Paolo Ruggieri; Muhammad Adnan Abid; Javier García-Serrano; Carlo Grancini; Fred Kucharski; Salvatore Pascale; Danila Volpi (Climate Dynamics, 2024)
A fully-coupled general circulation model of intermediate complexity is documented. The study presents an overview of the model climatology and variability, with particular attention to the phenomenology of processes that are relevant for the predictability of the climate system on seasonal-to-decadal time-scales. It is shown that the model can realistically simulate the general circulation of the atmosphere and the ocean, as well as the major modes of climate variability on the examined time-scales: e.g. El Niño-Southern Oscillation, North Atlantic Oscillation, Tropical Atlantic Variability, Pacific Decadal Variability, Atlantic Multi-decadal Variability. Potential applications of the model are discussed, with emphasis on the possibility of generating sets of low-cost large-ensemble retrospective forecasts. We argue that the presented model is suitable to be employed in traditional and innovative model experiments that can play a significant role in future developments of seasonal-to-decadal climate prediction.

Calibrated probabilistic sub-seasonal forecasting for Pakistan’s monsoon rainfall in 2022 - Bohar Singh; Muhammad Azhar Ehsan; Andrew W. Robertson (Climate Dynamics, 2024)

Moisture sources for precipitation variability over the Arabian Peninsula - Matthew F. Horan; Fulden Batibeniz; Fred Kucharski; Mansour Almazroui; Muhammad Adnan Abid; Joshua S. Fu; Moetasim Ashfaq (Climate Dynamics, 2023)
We apply the Lagrangian-based moisture back trajectory method to two reanalysis datasets to determine the moisture sources for wet season precipitation over the Arabian Peninsula, defined as land on the Asian continent to the south of the Turkish border and west of Iran. To accomplish this, we make use of the evaporative source region between 65°W–120°E and 30°S–60°N, which is divided into twelve sub-regions. Our comparison of reanalyses and multiple observations allows us to validate datasets and highlight broad-scale similarities in characteristics, notwithstanding some inconsistencies in the southwest AP. The results indicate north-to-south spatiotemporal heterogeneity in the characteristics of dominant moisture sources. In the north, moisture for precipitation is mainly sourced from midlatitude land and water bodies, such as the Mediterranean and Caspian Seas. Areas further south are dependent on moisture transport from the Western Indian Ocean and parts of the African continent. The El Niño-Southern Oscillation (ENSO) exhibits an overall positive but sub-seasonally varying influence on the precipitation variability over the region, with noticeable moisture anomalies from all major source regions. A significant drying trend exists over parts of the Peninsula, which both reanalyses partially attribute to anomalies in the moisture advection from the Congo Basin and South Atlantic Ocean. However, considerable uncertainty in evaporation trends over the terrestrial evaporative sources in observations warrants additional modeling studies to further our understanding of key processes contributing to the negative trends.

Performance evaluation of CMIP6 GCMs for the projections of precipitation extremes in Pakistan - Zulfiqar Ali; Mohammad Magdy Hamed; Mohd Khairul Idlan Muhammad; Zafar Iqbal; Shamsuddin Shahid (Climate Dynamics, 2023)

Spatio-temporal snow cover change in the early twenty-first century using improved MODIS dataset: a case study of District Hunza, Pakistan - Muhammad Farhan Ul Moazzam; Ghani Rahman; Kokab Saba Ali; Byung Gul Lee (Climate Dynamics, 2023)

On ranking climate factors affecting the living organisms based on paired comparison model, a Bayesian approach - Khalil Ullah; Muhammad Aslam; Nasir Abbas; Syed Irfan Shah (Climate Dynamics, 2023)

Spatiotemporal characteristics of meteorological drought variability and trends (1981–2020) over South Asia and the associated large-scale circulation patterns - Irfan Ullah; Xieyao Ma; Jun Yin; Abubaker Omer; Birhanu Asmerom Habtemicheal; Farhan Saleem; Vedaste Iyakaremye; Sidra Syed; Muhammad Arshad; Mengyang Liu (Climate Dynamics, 2023)

Seasonal predictability of Ethiopian Kiremt rainfall and forecast skill of ECMWF's SEAS5 model - Muhammad Azhar Ehsan; Michael K. Tippett; Andrew W. Robertson; Mansour Almazroui; Muhammad Ismail; Tufa Dinku; Nachiketa Acharya; Asher Siebert; Jemal Seid Ahmed; Asaminew Teshome (Climate Dynamics, 2021)

Potential predictability of boreal winter precipitation over central-southwest Asia in the North American multi-model ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui (Climate Dynamics, 2020)

Long-term ENSO relationship to precipitation and storm frequency over western Himalaya–Karakoram–Hindukush region during the winter season - Shahzad Kamil; Mansour Almazroui; In-Sik Kang; Muhammad Hanif; Fred Kucharski; Muhammad Adnan Abid; Fahad Saeed (Climate Dynamics, 2019)

Potential predictability of Arabian peninsula summer surface air temperature in the North American multimodel ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui; Muhammad Ismail; Michael K. Tippett (Climate Dynamics, 2019)

The possible physical mechanism for the EAP–SR co-action - Zhiqiang Gong; Guolin Feng; Muhammad Mubashar Dogar; Gang Huang (Climate Dynamics, 2018)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

Are Karakoram temperatures out of phase compared to hemispheric trends? - Fayaz Asad; Haifeng Zhu; Hui Zhang; Eryuan Liang; Sher Muhammad; Suhaib Bin Farhan; Iqtidar Hussain; Muhammad Atif Wazir; Moinuddin Ahmed; Jan Esper (Climate Dynamics, 2017)

Spatio-statistical analysis of temperature fluctuation using Mann–Kendall and Sen’s slope approach - Atta-ur-Rahman; Muhammad Dawood (Climate Dynamics, 2017)

Historical and projected changes in the Southern Hemisphere Sub-tropical Jet during winter from the CMIP5 models - Sheeba Nettukandy Chenoli; Muhammad Yunus Ahmad Mazuki; John Turner; Azizan Abu Samah (Climate Dynamics, 2017)

Karakorum temperature out of phase with hemispheric trends for the past five centuries - Muhammad Usama Zafar; Moinuddin Ahmed; Mukund Palat Rao; Brendan M. Buckley; Nasrullah Khan; Muhammad Wahab; Jonathan Palmer (Climate Dynamics, 2016)